The Changing Dynamics of Bisexual Men's Lives Social Research Perspectives - Anderson, Eric.; McCormack, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This important book provides unique new knowledge on the lived experience of openly bisexual men without medicalizing or pathologizing them. Presenting research from sexology, sociology, and psychology, it features extensive findings on the sexual, social, romantic, and emotional behaviors of the 90 men interviewed in the U.S. and U.K. Issues and challenges are examined in such areas as identity and self-concept, along with the burden of social erasure and the paradox of stigma from both the gay and straight communities. However, the research reveals evidence of a recent cultural transition toward acceptance of bisexual identity and behavior, with younger bisexual men experiencing better social lives and increased recognition of the legitimacy of bisexuality. Among the topics covered: Examining the components of sexuality. Measuring and surveying bisexuality. Bisexual burden Demonstrating a generational cohort effect Expansion of gendered boundaries. Erosion of the one-time rule of homosexuality. Coming out in the 21st century. Bringing clarity and focus beyond the gender binary$1 (Band compelling insights into why society and science have trouble shedding that paradigm$1 (BThe Changing Dynamics of Bisexual Men$1 (Bs Lives will interest sexuality scholars, sexologists, and social scientists studying the social aspects of sexuality.s
Introduction -- Bisexuality: It's Complicated -- Measuring and Surveying Bisexuality -- Bisexuality as a Unique Social Problem -- The Gendering of Sexuality -- Taking Bisexual Research to the Streets -- How Bisexual are our Bisexuals? -- Challenging Identities, Changing Identifications -- Coming Out with 20th Century Baggage -- Coming out in the 21st Century -- Bisexual Relationships -- Conclusions.
Keywords: Psychology; Sociology; Psychotherapy; Counseling; Sexual behavior; Sexual psychology; Sex (Psychology).; Gender expression; Gender identity; Psychology; Sexual Behavior; Gender Studies; Psychotherapy and Counseling; Electronic books